Identifikasi Penyebab Penyakit Bercak Daun Mycosphaerella pada Tanaman Stroberi (Fragaria sp.) di Bali dan Potensi Pengendaliannya dengan Jamur Antagonis secara In Vitro - ANDRAWINA, GUSTI AYU DWITA; WIRYA, GUSTI NGURAH ALIT SUSANTA; SUNITI, NI WAYAN; SUPUTRA, I PUTU WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Identification of Pathogenic Fungi causes Mycosphaerella Leaf Spot on Strawberry Plants ( Fragaria sp.) in Bali and Control Potential with Antagonist Fungi Strawberry ( Fragaria sp.) is a fruit cultivation plant that develops in Indonesia and has attractiveness and high economic value. Strawberry plants that grow at the center of strawberry production in Bali show symptoms of pathogenic fungus attack. Symptoms caused by the presence of brownish purple spots with a white center on the leaves. The purpose of this study was to identify pathogenic fungi that caused Mycosphaerella leaf spot disease on strawberry plants located at the center of strawberry production in Bali. The activities carried out in this study were (1) sampling and calculating the percentage of  Mycosphaerella leaf spot disease on strawberry plants, (2) isolation of pathogenic fungi from symptomatic leaves of strawberry plants, (3) pathogenicity testing, (4) identification of pathogenic fungi, and (5) test the potential inhibition of antagonistic fungi against pathogenic fungi. This research was conducted in Candi Kuning and Br Kembang Merta Village, Tabanan Regency and Pancasari Village, Buleleng Regency, and continued at the Plant Disease Laboratory, Faculty of Agriculture, Udayana University. The results of this study were successful in identifying Mycosphaerella fragariae as a pathogen causing leaf spot disease on strawberry plants in Bali and the potential for biological control by utilizing antagonistic fungi in vitro showed that Trichoderma viride, Trichoderma asperellum, Gliocladium sp . can suppress the growth of pathogenic fungi in strawberry plants of > 90%, Trichoderma harzianum and Trichoderma koningii up to >80%.